Contamination Rate of Lead in Pigeon (Columbia livia) at Semarang City - Indradji, M; Yuwono, E; Santosa, EB (ANIMAL PRODUCTION, 2000)
The aim of this research was to find out the lead concentration in some pigeon tissues in Semarang city. Fifty four pigeons 4-8 weeks old, which collected from 4 locations in Semarang were devided into 4 groups. Group I (15 pigeons) were obtained from the bird markets, group II (15 pigeons) were obtained from who sale fried birds, and group III (14 pigeons) were collected from the bird owners who look after the birds extensively (not in cages), then group IV (10 pigeons) were obtained from the bird owners who look after the birds intensively (in cages). All pigeons were euthanasia by chloroform then necropsied. A part of tissues eg: muscle, lung, liver and kidney were collected for lead examination by using Atomic Absorpsion Spectrophotometer (AAS). The result of the experiment showed that muscle, lung, liver and kidney pigeons were contaminated by lead, and lead concentration of kidney were higher (P< 0.05) than 0,1 ppm. Location of pigeons were not significant (P>0.05) with lead concentration in tissues pigeons. (Animal Production 2(2): 69-74 (2000)Â Key words : lead, pigeon, Semarang city